2014
DOI: 10.1111/ijfs.12670
|View full text |Cite
|
Sign up to set email alerts
|

Sensory study of different sodium chloride substitutes in aqueous solution

Abstract: The reduction of salt (sodium chloride) in food is one of the major challenges facing the food industry today and is motivated by the positive association between dietary salt intake and some diseases. Thus, the objectives of this study were to determine the equivalent amount of different sodium chloride replacements required to promote the same degree of ideal saltiness in aqueous solution and to study the sensory profile of sodium chloride and its substitutes using temporal dominance of sensations (TDS) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
14
1
2
Order By: Relevance
“…These values correspond to a saltiness potency of KCl in the range of 0.20–0.56 (average = 0.42), which is lower to that reported by other authors. Feltrin et al () reported that the saltiness of a KCl aqueous solution was 75% the saltiness of a 0.75% aqueous solution of NaCl. Similarly, Da Silva, de Souza, Pinheiro, Nunes, and Freire () estimated the saltiness potency of KCl in cream cheese as 0.83.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values correspond to a saltiness potency of KCl in the range of 0.20–0.56 (average = 0.42), which is lower to that reported by other authors. Feltrin et al () reported that the saltiness of a KCl aqueous solution was 75% the saltiness of a 0.75% aqueous solution of NaCl. Similarly, Da Silva, de Souza, Pinheiro, Nunes, and Freire () estimated the saltiness potency of KCl in cream cheese as 0.83.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the biggest drawback of using sodium replacers and explains why partial substitutions of NaCl by KCl are generally used to reduce the sodium content of foods. In this sense, there is general agreement on the fact that KCl does not only elicit salty taste but also undesirable flavors, such as bitterness and metallic flavor, when used above a given concentration (Feltrin, Rios de Souza, Goncalves Saraiva, Nunes, & Marques Pinheiro, ; Gelabert, Gou, Guerrero, & Arnau, ; Gou, Guerrero, Gelabert, & Arnau, ). Nevertheless, the amount of KCl to be added without causing undesirable changes on the sensory profile of sodium reduced foods markedly depends on the product category, its sensory characteristics and complexity.…”
Section: Introductionmentioning
confidence: 97%
“…Mixtures of KCl, NaCl, and MSG from the experimental design were planned considering its salting power and making its salty taste confer equivalent to 1.6% NaCl in shoestring potatoes. However, this should only be considered as a theoretical approach, because the intensity of the salty taste of the mixtures can be altered by synergistic or antagonistic effects of these substances, by their taste peculiarities, and the fact that their salting powers have been determined in aqueous solution (Feltrin and others ), different matrix of shoestring potatoes. Then, the regression equation for the ideal salting can confirm that the optimized formulation, in terms of global acceptance, presents ideal salting.…”
Section: Resultsmentioning
confidence: 99%
“…Potassium chloride was considered to have 75% and monosodium glutamate 60% of the reference salting power in this product. The salting potency of these 2 substitutes was determined in a previous study (Feltrin and others ). Thus, the concentration, in percentage, of each salt used in each formulation, according to the proposed design, has been calculated (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation